URBAN PLANNING, MANAGEMENT AND HOUSING POLICIES IN EUROPEAN RIVER CITIES AND CITY OF BELGRADE - CASE STUDY - Milenković, Dejan (Political Review, 2024)
As a consequence of the lack of public policies and legal framework, and then the non-compliance with laws and regulations related to the use of rivers and coasts, the development of floating communities from their creation until today in Belgrade, has flowed predominantly from the bottom up, i.e. from individual and often illegal actions individuals to the gradual and increasingly current determination and then the implementation of public policies and the arrangement of the river area. Comparatively, some European cities on rivers and canals have, in the last few decades, increasingly paid attention to the careful planning of river and canal management and the potential opportunities for the realization of urban green housing projects through the creation of sustainable floating micro-river communities on them. And the city of Belgrade gradually adapts to these needs. In the city of Belgrade, in addition to a large number of examples of bad practice of “floating communities” there are also some good examples of “micro river space” arrangement and good practice of living and living in an ecologically acceptable natural environment on the water. This is the case of the river island of Ada Međica in Belgrade, which can serve as a “good case” for other European cities on rivers. It is a sustainable community characterized by the symbiosis of people and the environment, where the strength of a small river community contributes to the preservation of the environment, the achievement of ecological balance and urban green living in a natural environment.
Keywords: urban policies; cities; rivers and canals; micro public space; floating communities; urban green housing